Review on biomass gasification: Gasifiers, gasifying mediums, and operational parameters - Somya Mishra (KeAi Communications Co., Ltd., 2021)
The burning of fossil fuels causes the average global surface temperature to rise every year by 0.6 to 0.9 K between 1906 and 2005 causing massive ecological imbalance and an increase in global warming as reported by Intergovernmental Panel on Climate Change (IPCC). Biomass gasification is an enhanced and mature technology that has the capability of replacing fossil fuels. Despite the presence of vast literature, biomass technology still needs improvement. This paper discusses the critical overview of biomass gasification, the technologies embedded, and the deciding parameters for producing valuable products such as syngas, bio-fuels, bio-char, power, heat, and fertilizer, which can be further utilized in power generation units, and fuel-cell technologies. The paper assimilates the information available in past studies of biomass gasification and presents a comprehensive review of various gasifiers and gasifying mediums employed, followed by introducing supercritical water (SCW) gasification. Future directions for readers are also discussed.